DEIXIS IN MALEFICENT MOVIE SCRIPT - Wiguna, Andi; Anggraeni, Hera; Nuramalia, Reyka; Sadikin, Irma Savitri (PROJECT (Professional Journal of English Education), 2018)
This study is an attempt to analyze types of deixis those are: personal deixis ( first. Second, and third person deixis), place deixis, time deixis, and discourse deixis.  This study only focused on the movie script. This study was purposed to find out the types and the dominant of deixis are used in  Maleficent Movie Script. This script got from the internet. The study applied descriptive qualitative method.  Steps of analyses the data, it applied was the first, this study looked for the movie, the second, this study watched the movie, then, looked for the movie script of the movie “Black Swan”, the fourth, this study identified the sentence of the movie script based on four types of deixis. The result of this research shows dominant in person deixis: I, you, we, he, she, our, king Stephan, because from the result personal deixis in the movie script is dominant from the place, time, and discourse deixis.